Dynamics of organizational behavior in the adoption of digital technology: A case study at SMA Negeri 3 Pontianak - Noviah Dwi Putranti; Marinu Waruwu; Luhur Wicaksono (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
The growing integration of digital technology in education has increasingly influenced organizational behavior, legal considerations, and ethical responsibilities within schools. This study examines the dynamics of organizational behavior in the implementation of digital technology at SMA Negeri 3 Pontianak, focusing on the challenges, adaptation processes, and implications for decision-making and institutional strategy. Using a descriptive qualitative method with an inductive approach, data were collected from 154 participants—129 students, 20 teachers, and 5 education personnel—selected through purposive sampling. Data collection techniques included interviews, questionnaires, observations, and document analysis, followed by thematic categorization and triangulation to validate findings. The results reveal significant behavioral changes among school members, characterized by increased collaboration, creativity, flexibility, and efficiency in learning and administrative processes. Digital technology has strengthened communication patterns and facilitated blended learning practices. However, challenges persist in terms of infrastructure limitations, uneven digital literacy, and resistance to technological change. The study highlights the importance of continuous training, supportive leadership, and adaptive management strategies to sustain digital transformation. Overall, the findings underscore that digital technology adoption not only reshapes organizational structure and culture but also enhances the school’s capacity to respond to the demands of the digital era.